2015
DOI: 10.1039/c5ta02942b
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen evolution catalyst on an antimony doped tin oxide nanowire structured support for proton exchange membrane liquid water electrolysis

Abstract: Porous Sb–SnO2 nanowires were synthesized as a support for IrO2 by an electrospinning method. The thus prepared catalyst exhibits enhanced mass activity toward OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
79
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 78 publications
(17 reference statements)
13
79
2
4
Order By: Relevance
“…Of the investigated oxides, mesoporous ATO ( meso ‐ATO) showed the highest conductivity (0.29 S cm −1 ) and a highly stable cyclability (>10 000 cycles) . Similar results (0.83 S cm −1 ) were reported for electrospun crystalline ATO nanowires (nws) . The outstanding stability of IrO 2 nanodendrites and IrNi oxide core–shell particles mentioned in Section 4.3 is further improved when supported on nanostructured ATO ,.…”
Section: Degradation Mechanisms and Mitigation Strategiessupporting
confidence: 64%
“…Of the investigated oxides, mesoporous ATO ( meso ‐ATO) showed the highest conductivity (0.29 S cm −1 ) and a highly stable cyclability (>10 000 cycles) . Similar results (0.83 S cm −1 ) were reported for electrospun crystalline ATO nanowires (nws) . The outstanding stability of IrO 2 nanodendrites and IrNi oxide core–shell particles mentioned in Section 4.3 is further improved when supported on nanostructured ATO ,.…”
Section: Degradation Mechanisms and Mitigation Strategiessupporting
confidence: 64%
“…This finding is in contrastw ith the often reported stable but poor OER performance of crystalline IrO 2 -based compounds produced through more classical calcination routes. [14] In addition to optimized catalyst morphology by dispersion of Ir particles on as uitable support, producingt he "right" chemicals tate of Ir is no less critical to the OER performance of the catalytic system.E arly electrochemical studies showed that metallici ridium is inefficient in OER and needs to be activated under oxidative conditions. anodic potentials in chlorine-free acidic electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The Tafel slope for the conventional catalyst at E < 1.43 V was 63 mV, which is close to the 60 mV slope commonly reported for IrO 2 -based electrodes in sulfuric acid solution. 14,18,19,32 The stability test of the IrO x /Nb-SnO 2 catalyst during constant current OER was carried out preliminary in air-saturated 0.1 M HClO 4 solution at 80…”
Section: Electrochemical Characterization Of Iromentioning
confidence: 99%
“…The OER activities of iridium and/or ruthenium oxide nanoparticle (or nanodendrite) catalysts supported on antimony-doped tin oxide (Sb-SnO 2 ), which exhibited a relatively high electronic conductivity, have been examined by several groups. [14][15][16][17][18][19] However, to our knowledge, the microstructures of neither the noble metal catalysts nor the supports have been controlled at the nanoscale.…”
mentioning
confidence: 99%